A critical evaluation on nuclear safety properties of novel cadmium oxide-rich glass containers for transportation and waste management: Benchmarking with a reinforced concrete container - ALMisned, Ghada; Baykal, Duygu Sen; Kilic, G.; Ilik, E.; Zakaly, Hesham M.H.; Ene, Antoaneta; Tekin, H. O. (Frontiers in Physics, 2022)
We examine the nuclear safety properties of a newly designed cadmium oxide-rich glass container for nuclear material to a bitumen-reinforced concrete container. Individual transmission factors, detector modelling, and energy deposition (MeV/g) in the air are calculated using MCNPX (version 2.7.0) general purpose Monte Carlo code. Two container configurations are designed with the material properties of CdO-rich glass and Concrete+Bitument in consideration. First, individual transmission factors for 60Co and 137Cs radioisotopes are calculated. To evaluate potential environmental consequences, energy deposition amounts in the air for 60Co and 137Cs are also determined. The minimum gamma-ray transmission rates for two container types are reported for a CdO-rich glass container. In addition, the quantity of energy deposition is varied depending on the container type, with a lower value for CdO-rich glass container. The 40% CdO-doped glass container provides more effective safety than the Cement+Bitumen container, according to the overall findings. In conclusion, the utilization of CdO-doped glass material along with its high transparency and advanced material properties may be a significant and effective option in areas where concrete is required to assure the safety of nuclear materials.